Simulating the impact of an educational and digital approach using patient journey modelling to overcome practical challenges in the management of chronic spontaneous urticaria in Germany - von Kiedrowski, Ralph; Berneburg, Mark; Biermann, Mona; Bonnekoh, Hanna; Fritz, Michael; Tischler, Max; Metz, Martin; Volc, Sebastian; Wagner, Nicola; Zink, Alexander; Nathan, Petra (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and Objective: Despite the availability of guidelines and effective escalation therapies, chronic spontaneous urticaria (CSU) is often inadequately treated in Germany. Implementation science can help to transfer evidence-based care into practice. The aim of this work is to analyze practical challenges, develop intervention strategies and simulate their potential impact on patient outcomes. Methodology: A multi-stage approach with literature research, market research, expert interviews and focus groups with healthcare professionals enabled a comprehensive context analysis. Based on this, intervention strategies were developed and simulated using a patient journey model. The focus was on an educational program and telemedicine monitoring. Results: CSU management is hampered by delayed diagnosis and underutilization of available therapies. Barriers include lack of knowledge of diagnostic tools, lack of referral standards and structural barriers to the use of patient-reported outcomes. Two strategies were proposed: a training program to improve diagnostics and therapy and telemedicine to optimize monitoring. Simulations show that educational measures could increase diagnosis and treatment rates and digital approaches could reduce waiting times. Conclusion: The study systematically identifies barriers in CSU care and uses a patient journey approach to show the potential effects of targeted implementation strategies. Educational measures in particular could significantly improve care.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Barriers; chronic spontaneous urticaria; education; implementation science; interventions; patient journey modelling; simulation; telemedicine